Physiological Role of Glutamate Dehydrogenase in Cancer Cells - Moreno-Sánchez, Rafael (Front Oncol, 2020)
[Formula: see text] increased growth rates and final densities of several human metastatic cancer cells. To assess whether glutamate dehydrogenase (GDH) in cancer cells may catalyze the reverse reaction of [Formula: see text] fixation, its covalent regulation and kinetic parameters were determined under near-physiological conditions. Increased total protein and phosphorylation were attained in [Formula: see text]-supplemented metastatic cells, but total cell GDH activity was unchanged. Higher V(max) values for the GDH reverse reaction vs. forward reaction in both isolated hepatoma (HepM) and liver mitochondria [rat liver mitochondria (RLM)] favored an [Formula: see text]-fixing role. GDH sigmoidal kinetics with [Formula: see text] , ADP, and leucine fitted to Hill equation showed n(H) values of 2 to 3. However, the K(0.5) values for [Formula: see text] were over 20 mM, questioning the physiological relevance of the GDH reverse reaction, because intracellular [Formula: see text] in tumors is 1 to 5 mM. In contrast, data fitting to the Monod–Wyman–Changeux (MWC) model revealed lower K(m) values for [Formula: see text] , of 6 to 12 mM. In silico analysis made with MWC equation, and using physiological concentrations of substrates and modulators, predicted GDH N-fixing activity in cancer cells. Therefore, together with its thermodynamic feasibility, GDH may reach rates for its reverse, [Formula: see text]-fixing reaction that are compatible with an anabolic role for supporting growth of cancer cells.